Implementasi Program Dalam Perilaku Menerapkan Gaya Hidup Bersih SDN Sukabumi 2 Probolinggo - Ani Anjarwati; Errina Dinda Festawanti; Yuni Wulandari; Faradella Rahmadhini; Muthmainnah; Vega Fakis Alhamni; Hasyim Muzadi (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
During the observation activities on a healthy lifestyle, the importance of maintaining cleanliness in the school environment and its surroundings. The purpose of implementing this program is to introduce students to maintaining cleanliness by washing their hands, disposing of garbage in its place, using healthy and nutritious food, and personal hygiene. To start a healthy lifestyle some students consider a tiring activity, a waste of time and other negative views. Based on the results of observations, it was concluded that SDN Sukabumi 2 grade 4 consisted of 30 students, quite understanding, and had implemented a clean and healthy lifestyle.